Conjugated Self-Assembled Monolayer as Stable Hole-Selective Contact for Inverted Perovskite Solar Cells - Zhang, Shuo; Wu, Ruihan; Mu, Chenkai; Wang, Yanbo; Han, Liyuan; Wu, Yongzhen; Zhu, Wei-Hong (ACS materials letters, 2022)
The alkyl linker-based self-assembled monolayer (SAM) has emerged as an efficient hole-selective contact (HSC) for inverted perovskite solar cells (PSCs). Despite being effective in hole-extraction and interfacial passivation, its hole-transporting capability is limited by the insulating alkyl linker, along with poor stability due to the isolated and nonconjugated electron-rich moiety. Here, we report a series of conjugated SAMs that exhibit excellent photo- and electrical stabilities. The conjugated molecular structure not only enhances charge transport but also stabilizes the electron-rich arylamines through electron/charge delocalization. Moreover, it enables convenient modulation of frontier orbital energy levels for interfacial band alignment. By scrutinization of the conjugation-linker and hole-transporting head, an optimal conjugated SAM (MPA-Ph-CA) in combination with the standard triple cation perovskite Cs0.05(FA0.92MA0.08)0.95Pb(I0.92Br0.08)3 achieved an efficient inverted PSC with a power conversion efficiency (PCE) of 22.53% (certified 22.12%). Moreover, the MPA-Ph-CA based devices showed excellent stability, retaining over 95% of their initial PCEs under one sun constant irradiation for 800 h. The synchronously enhanced efficiency and stability suggest that conjugated SAM-based HSCs are promising for further advancing inverted PSCs.